Rapid mass multiplication of Glomus mosseae inoculum as influenced by some biotic and abiotic factors - Bhowmik, Subrata Nath; Yadav, Gulab Singh; Datta, Mrinmay (Bangladesh Journal of Botany, 2018)
Rhodes grasses (Chloris gayana Kunth) inoculated with Glomus mosseae were grown under the influence of Azospirillum (biotic factor), IAA (abiotic factor) and Hoagland’s solution (abiotic factor). The effectiveness of each factor was evaluated by measuring mycorrhizal root colonization and spore numbers. The pot culture experiment was carried out under polyhouse condition and observations were recorded at 45, 90 and 120 days of plant growth. The harvest date finely influenced the size of mycorrhizal inoculum. But, all biotic and abiotic factors had a greater influence on root colonization and spore multiplication than harvest time. The agents on application in conjunction favourably enhanced root infection and spore multiplication as compared to their solo treatments, with Azospirillum + Hoagland’s solution application posing to be the best. This not only stimulated mycorrhizal development, but also accelerated the root growth.